Saving for Dowry : Evidence from Rural India - Anukriti, S.; Kwon, Sungoh; Prakash, Nishith (World Bank, Washington, DC, 2020)
The ancient custom of dowry, that is, bride-to-groom marriage payments, remains ubiquitous in many contemporary societies. This paper examines whether dowry impacted household decision making and resource allocation in rural India during 1986-2007. Utilizing variation in firstborn gender and dowry amounts across marriage markets, the paper finds that the prospect of higher dowry payments at the time of a daughter's marriage leads parents to save more in advance. The higher savings are primarily financed through increased paternal labor supply. This implies that people are farsighted; they work and save more today with payoff in the distant future.